Similarity or Variation? Employee Representation and Consultation Approaches amongst Liberal Market Economy Multinationals - McDonnell, Anthony; Boyle, Brendan; Bartram, Timothy; Stanton, Pauline; Burgess, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2015)
This paper engages with the varieties of capitalism literature to investigate the employee representation and consultation approaches of liberal market economy multinational companies (MNCs), specifically Australian, British and US MNCs operating in Australia. While the literature would suggest commonality amongst these MNCs, the paper considers whether the evidence points to similarity or variation amongst liberal market headquartered MNCs. The findings contribute to filling a recognized empirical gap on MNC employment relations practice in Australia and to a better understanding of within category varieties of capitalism similarity and variation. Drawing on survey data from MNCs operating in Australia, the results demonstrated that UK-owned MNCs were the least likely to report collective structures of employee representation. Moreover, it was found that Australian MNCs were the most likely to engage in collective forms of employee representation and made less use of direct consultative mechanisms relative to their British and US counterparts. In spite of the concerted individualization of the employment relations domain over previous decades, Australian MNCs appear to have upheld more long-standing national institutional arrangements with respect to engaging with employees on a collective basis. This varies from British and US MNC approaches which denotes that our results display within category deviation in the variety of capitalism liberal market economy typology. Just as Hall and Soskice described their seminal work on liberal market economy (LME) and coordinated market economy (CME) categories as a “work-in-progress” (2001: 2), we too suggest that Australia’s evolution in the LME category, and more specifically its industrial relations system development, and the consequences for employment relations practices of its domestic MNCs, may be a work-in-progress.